Resistance Training as a Non-Pharmacological Strategy in Chronic Diseases - Żukowiecka-Sęga, Dominika; Porada, Dagmara; Tłoczek, Wiktoria; Twardowska, Daria; Śliwa, Wiktoria; Jelonek, Barbara; Tomczak, Barbara; Wandzel, Małgorzata; Topolski, Kamil; Klubikowska, Karolina (Quality in Sport, 2026)
Introduction and purpose. Chronic non-communicable diseases (NCDs), such as cardiovascular disease and diabetes, are leading causes of global mortality. While pharmacological treatments remain standard, there is a shift toward lifestyle-based interventions. Historically, aerobic exercise was primarily recommended; however, contemporary evidence suggests that resistance training (RT) offers unique systemic benefits. This paper evaluates RT’s efficacy as a non-pharmacological strategy and analyzes its underlying biological mechanisms. Material and methods. A literature review was conducted using PubMed, Web of Science, and Google Scholar, focusing on meta-analyses and systematic reviews published between 2009 and 2025. A total of 31 academic sources were synthesized. Inclusion criteria focused on the impact of RT on metabolic, cardiovascular, musculoskeletal, and mental health in clinical populations. Results. The analysis indicates that RT is a potent modulator of metabolic health, reducing HbA1c levels and enhancing insulin sensitivity via GLUT4 translocation. In cardiovascular health, RT is associated with significant reductions in blood pressure and improved endothelial function. Furthermore, RT serves as the most effective countermeasure against sarcopenia and osteoporosis by stimulating muscle protein synthesis and bone mineral density. Evidence also highlights the "muscle-brain axis," where RT-induced myokines alleviate symptoms of depression and anxiety. Under proper supervision, RT is safe and effective for patients with multiple comorbidities. Conclusions. RT should be recognized as a cornerstone of chronic disease management, providing systemic benefits across metabolic and neurological health. Healthcare systems should integrate structured RT into standard clinical protocols. Addressing barriers such as lack of specialized medical training and patient accessibility remains essential for the successful implementation of this non-pharmacological strategy.